Age composition of Chukchi sockeye salmon Oncorhynchus nerka - Elena V. Golub’ (Известия ТИНРО, 2014)
Long-term data on age composition for Chukchi populations of sockeye salmon are presented. Spawners of 23 ages are recognized in the period 1970-2013 for 10 populations: 2+, 3+, 0.1+, 0.2+, 0.3+, 0.4+, 0.5+, 1.1+, 1.2+, 1.3+, 1.4+, 1.5+, 2.1+, 2.2+, 2.3+, 2.4+, 2.5+, 3.1+, 3.2+, 3.3+, 3.4+, 4.2+, and 4.3+. The brood stock basis is formed by five- and six-year fish of 1-2-year freshwater feeding and 3-year marine feeding. The greatest diversity in the age composition is observed at the northern limit of the Asian sockeye salmon natural habitat - i.e. in the Seutakan and Achchen lake-river systems. The spawners dropped into the sea at the age of 0+ and 1+ years are more common in the populations with prevailing limnophilous forms of sockeye (rivers Khatyrka, Tumanskaya and Anadyr, Seutakan lake-river system), and the spawners dropped at the age 2+ and 3+ years - in the populations with domination of its rheophilous form (Meinypilgyn lake-river system, Orianda and Amaam lagoons). As compared with the sockeye salmon from central spawning areas of the habitat, the Chukchi sockeye has more complicated age composition of reproductive part of stocks, greater duration of marine feeding, females predominance among fast-maturing fish returning after 2 years of marine life, higher portion of males in senior age groups, and minor level of kokanee salmon and jacks. Brief description of spawning and/or feeding ponds for Chukchi sockeye salmon is presented.